When Prosecutors Politick: Progressive Law Enforcers Then and Now - Green, Bruce A. (2020)
A new and recognizable group of reform-minded prosecutors has assumed the mantle of progressive prosecution. The term is hard to define in part because its adherents embrace a diverse set of policies and priorities. In comparing the contemporary movement with Progressive Era prosecutors, this Article has two related goals. First, it seeks to better define progressive prosecution. Second, it uses a historical comparison to draw some lessons for the current movement. Both groups of prosecutors were elected on a wave of popular support. Unlike today’s mainstream prosecutors who tend to campaign and labor in relative obscurity, these two sets of prosecutors received a good deal of popular attention and support. The Progressive Era reformers introduced the notion promoted by current progressive prosecutors that crime is a social phenomenon, which community services are better equipped to address than prisons. The Progressive Era movement also sought to implement professional norms and practices to promote the values of fairness and proportionality. Contemporary progressive prosecutors inherit this legacy but tend not to emphasize these professional values. The Article concludes that the professional values championed during the Progressive Era are critical, in conjunction with new programs and policies, to ensure that as innovation helps achieve social justice, prosecution remains in the hands of those committed to fair and even-handed justice